WDVV equations, Darboux-egoroff metric and the dressing method - Aratyn, H.; Gomes, J. F. [UNESP]; van de Leur, J. W.; Zimerman, A. H. [UNESP] (My University, 2002)
Dressing technique is used to construct commuting Lax operators which provide an integrable (canonical) structure behind Witten–Dijkgraaf–Verlinde–Verlinde equations. The commuting flows are related to the isomonodromic flows. Examples of the canonical integrable structure are given in two- and three-dimensional cases. The three-dimensional example is associated with the rational Landau-Ginzburg potentials.
Keywords: Darboux-Egoroff metric; Tau function; WDVV Equations